2009
DOI: 10.1073/pnas.0906941106
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amygdalar PKA by β-arrestin-2/phosphodiesterase-4 complex is critical for fear conditioning

Abstract: ␤-arrestins, key regulators of receptor signaling, are highly expressed in the central nervous system, but their roles in brain physiology are largely unknown. Here we show that ␤-arrestin-2 is critically involved in the formation of associative fear memory and amygdalar synaptic plasticity. In response to fear conditioning, ␤-arrestin-2 translocates to amygdalar membrane where it interacts with PDE-4, a cAMP-degrading enzyme, to inhibit PKA activation. Arrb2 ؊/؊ mice exhibit impaired conditioned fear memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Similar results were observed in GSK3 mutant mice, which display a 50% reduction in the expression of this kinase (Hoeflich et al, 2000). With respect to β-arrestin-2, recent findings show that this protein might be also involved in neurogenesisdependent and -independent mechanisms Li et al, 2009). Using the "CORT model", it was shown that fluoxetine reversed the neurogenic deficit induced by glucocorticoid elevation and restored expression of β-arrestin-1 and -2 that were blunted by chronic corticosterone ).…”
Section: Current Hypotheses On the Molecular And Cellular Bases Of Nosupporting
confidence: 65%
“…Similar results were observed in GSK3 mutant mice, which display a 50% reduction in the expression of this kinase (Hoeflich et al, 2000). With respect to β-arrestin-2, recent findings show that this protein might be also involved in neurogenesisdependent and -independent mechanisms Li et al, 2009). Using the "CORT model", it was shown that fluoxetine reversed the neurogenic deficit induced by glucocorticoid elevation and restored expression of β-arrestin-1 and -2 that were blunted by chronic corticosterone ).…”
Section: Current Hypotheses On the Molecular And Cellular Bases Of Nosupporting
confidence: 65%
“…It is well established that cAMP signalling plays a central role in neuronal plasticity and learning [43,44]. This includes both acute effects mediated through activation of PKA and long-term changes involving transcriptional regulation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Either too much activity or too little activity results in learning deficits, suggesting the existence of complex compensatory feedback mechanisms. Accordingly, modulators of cAMP phosphodiesterases (PDEs) have been successfully used to correct for memory deficits induced by up-or downregulations of PKA signalling [43,48]. Mice expressing a constitutively active form of Gas in forebrain neurons exhibit lower brain cAMP levels because of an increase in PKA-dependent PDE activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Fear conditioning activates the PKA signaling pathway that is significant inhibited by extinction (Isiegas et al, 2006;Li et al, 2009;Moita et al, 2002;Schafe et al, 1999). Genetic inhibition of PKA activity or pharmacological inhibition of the anchoring of PKA to A-kinase anchoring proteins facilitated extinction learning (Nijholt et al, 2008).…”
Section: Mechanism That Underlies the Role Of Hippocampal Ne In The Pmentioning
confidence: 99%